PARTISIPASI SEBAGAI STRATEGI PEMBERDAYAAN PETANI MISKIN MELALUI PROGRAM INTEGRASI JAGUNG DAN TERNAK - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008)
Empowerment through participatory strategic of peasant were important keywords in rural agriculture development program. Participatory was a strategic approach to make rural peasant empowerment. Empowerment is a target and participatory are the tools of integration maize livestock. With that program, the peasant can do breeder selection; IB technology; organic fertilizer; handle livestock feed problem; etc. Usefully of peasant participatory was made them to be empowerment and handled marginal agro ecosystem farming problem. Maize-livestock integration is a program making dry farming become potential to increase the breeder farming earnings, and done this program what good and the correctness can increase maize product, diversification crops, and improvement household income.
Keywords: Empowerment, Participatory, Maize Livestock Integration, Peasant, Poor Farmer.